Cognitive load at encoding hurts memory selectivity. Issue 7 (July 2023) - Dubravac, Mirela; Meier, Beat
People remember more task-relevant information than task-irrelevant information, and this difference can be conceptualised as memory selectivity. Selectively attending and remembering relevant information is a key ability for goal-directed behaviour and is thus critical for leading an autonomous life. In the present study, we tested the influence of cognitive load on memory selectivity. Specifically, we investigated the effects of task switching, stimulus presentation duration, and preparation time during incidental learning in five experiments ( N = 351). For the study phase, we used two established task switching paradigms (cued and alternating runs). Participants were presented with picture–word pairs on which they performed one of two classification tasks. Depending on the task, participants had to attend to the picture or to the word. In a subsequent surprise recognition test, we assessed how well they remembered the targets and distractors. After 1 day or 1 week, a second recognition test assessed the longevity of the effects. Results showed that task switches (vs task repetitions), short (vs until response) stimulus duration, and short (vs long) preparation time reduced memory selectivity. The effect of preparation time was significant only in cued task switching but not in the alternating runs paradigm, highlighting the importance of advance cues for preparation effects on memory. With longer retention intervals, the effects washed out. In conclusion, higher cognitive load leads to lower selective attention and, consequently, to lower memory selectivity. The present study provides links between theories of attention, cognitive control, and memory.